Emotional intimate partner violence experienced by men in same-sex relationships. Issue 10 (2nd October 2016) - Woodyatt, Cory R.; Stephenson, Rob
Abstract: Intimate partner violence research has focused almost exclusively on physical and sexual intimate partner violence in opposite-sex relationships, paying little attention to the intimate partner violence experienced by men in same-sex relationships. Emerging research focusing on intimate partner violence among male-male couples has focused largely on physical and sexual violence, with little consideration of the unique forms of emotional violence experienced by gay men. Ten focus-group discussions with gay and bisexual men were conducted to examine perceived typologies, antecedents and experiences of emotional violence that occur between male partners. Participants described emotional violence as the most threatening form of intimate partner violence, driven largely by factors including power differentials, gender roles and internalised homophobia. Results indicate that gay and bisexual men perceive emotional intimate partner violence to be commonplace. A better understanding of emotional violence within male-male relationships is vital to inform intimate partner violence prevention efforts and the more accurate measurement of intimate partner violence for gay men.